Linguocultural Elements in Text of Novel “On Eve” and Analysis of Their Translated Equivalents in Serbian - M. B. Pavlović-Šajtinac; I. S. Tyapkov (Научный диалог)
The article is devoted to the issue of cross-cultural communication and difficult cases of translation into Serbian and Croatian languages of lexical and phraseological units from Ivan Turgenev’s novel “On the Eve”. The relevance of this issue lies in the analysis of translation as an act of communication, during which the linguistic worldview of the people is represented. The material for the study was translations of the novel “On the Eve” into Serbian and Croatian languages from different years, which are close to Russian. As a tertium comparationis, we considered the translation of this work into English. The authors analyzed forms of address and non-equivalent vocabulary, as well as idioms, which translators represented differently in their translation options. As a result of the study, it was found that difficulties arise in translating words that denote concepts related to the cultural-historical Russian context. It is shown that Serbian translators often try to take historical facts into account and give comments when there are no equivalents in their native language. It is noted that there is currently a need for a Russian-Serbian linguistic and cultural dictionary that will help a specialist create an adequate translation variant close to the original.